2022
DOI: 10.1038/s41598-022-12737-w
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of Gαq sequesters specific transcripts into Ago2 particles

Abstract: The Gαq/phospholipase Cβ1 (PLCβ1) signaling system mediates calcium responses from hormones and neurotransmitters. While PLCβ1 functions on the plasma membrane, there is an atypical cytosolic population that binds Argonaute 2 (Ago2) and other proteins associated with stress granules preventing their aggregation. Activation of Gαq relocalizes cytosolic PLCβ1 to the membrane, releasing bound proteins, promoting the formation of stress granules. Here, we have characterized Ago2 stress granules associated with Gαq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…In further studies, we found that the stress granules formed in PC12 cells in response to Gαq activation have a district composition and sequester only two mRNAs. 39 The underlying mechanisms that control stress granule composition are unclear and are under investigation.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In further studies, we found that the stress granules formed in PC12 cells in response to Gαq activation have a district composition and sequester only two mRNAs. 39 The underlying mechanisms that control stress granule composition are unclear and are under investigation.…”
Section: ■ Resultsmentioning
confidence: 99%
“…We followed the size and number of ALG-1, the worm equivalent of Ago2, with single and repeated Gαq stimulation whose trends were similar, but smaller than those seen with G3BP1 consistent the idea that ALG-1 stress granules are a subset of G3BP1 stress granules (18). In cultured cells, Gαq activation promotes the formation of Ago2 stress granules that protect and sequester two RNAs, Chgb and ATP5f1b (see (26)). We tested whether this is the case in C.elegans neurons.…”
Section: Discussionmentioning
confidence: 99%
“…While G3BP1 is the de facto stress granule marker, Ago2 is a binding partner of PLCβ and is released as PLCβ binds to Gαq upon stimulation (18, 26). We followed the size and number of ALG-1, the worm equivalent of Ago2, with single and repeated Gαq stimulation whose trends were similar, but smaller than those seen with G3BP1 consistent the idea that ALG-1 stress granules are a subset of G3BP1 stress granules (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous pull-down and mass spectrometry studies indicate that neither Egr-1 or TRBP are direct or indirect binding partners of PLCβ1 (29). However, TRBP is a component of Ago2 stress granules that form when cytosolic levels of PLCβ1 are lowered (30). We tested the idea that cytosolic PLCβ1 regulates the availability of TRBP for Egr-1 binding which may stabilize the cytosolic localization of Egr-1.…”
Section: Cytosolic Plcβ1 Regulates Egr-1 / Trbp Associationmentioning
confidence: 96%